Frailty Score as a Predictor of Outcomes in Geriatric Patients with Isolated Hip Fractures. Issue 5 (May 2023) - Sang, Whiyie A.; Durrani, Hamza; Liu, Huazhi; Clark, Jason M.; Ferber, Laurence; Hagan, Joshua; Richards, Winston; Taylor, Dana; Watson, Carrie; Ang, Darwin
Background: Isolated hip fractures (IHFs) are a cause of morbidity and mortality in the geriatric population aged >65 years. Frailty has been identified as a determinant for patient outcomes in other surgical specialties. The purpose of this study is to determine if frailty severity is a predictor of outcomes in IHF in the geriatric population. Methods: This is a retrospective study in a state and ACS Level 2 trauma center. Patients with IHF were reviewed between January 2018 and January 2020. Primary outcome was in-patient mortality. Secondary outcomes include perioperative outcome measures such as UTI, HCAP, DVT, readmission, length of stay, ICU length of stay, nutritional status, and discharge destination. Patients were stratified into mild (1-2), moderate (3-5), and severe (5-7) frailty using the Rockwood Frailty Score (RFS). Clinical characteristics and outcomes were analyzed. Results: We identified 470 patients with IHF who were stratified by mild (N=316), moderate (N-123), and severe (N=31) frailty. Frailty worsened with increasing age (P < .0001). Those who were less frail were more likely discharged home (P < .04). Severely frail patients were more likely discharged to hospice (P < .01). Severely frail patients also were more likely to develop DVT (P < .04) and have poorer nutritional status (P < .02). There were no differences among groups for in-patient mortality. Conclusion: Severely frail patients are more likely to be malnourished at baseline and be discharged to hospice care. The RFS is a reliable objective tool to identify high-risk patients and guide goals of care discussion for operative intervention in isolated traumatic hip fractures.